Create a secrets sharing application and client in Go. (Manning Publications, 2022)
Amit Saha is a software engineer at Atlassian, located in Sydney, Australia. In this video, he introduces his project: https://www.manning.com/liveprojectseries/secrets-sharing-ser where you get hands-on experience building backend web applications with Go.